2018
DOI: 10.3823/820
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance pattern of Escherichia coli strains isolated from poultry farmers and poultry slaughterers in Morocco

Abstract: Aim: The objective of this study is to characterize the antibiotic resistance pattern of Escherichia coli isolates from the fecal samples of poultry workers (farmers and slaughterers), and to study the possible dissemination of resistant E. coli from poultry to humans. Methods:Sixty-four E. coli strains isolated from the fecal samples of poultry workers (33 from poultry farmers and 31 from poultry slaughterers) and 35 isolates from a control group workers were tested for antibiotic resistance by agar disk diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…Most of the E. coli strains that are isolated from swine and pig farm workers show high resistance to ampicillin, tetracycline, and sulfamethoxazole in both humans and livestock. These results are consistent with those of similar studies conducted in other countries [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 94%
“…Most of the E. coli strains that are isolated from swine and pig farm workers show high resistance to ampicillin, tetracycline, and sulfamethoxazole in both humans and livestock. These results are consistent with those of similar studies conducted in other countries [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 94%
“…The susceptibility test results showed a remarkable level of antimicrobial resistance to the first-line antibiotic treatments: aminopenicillins without beta-lactamase inhibitors (58.3%), chloramphenicol (23.9%), trimethoprim (32.2%), and trimethoprim-sulfamethoxazole (26%). An overall increase in ampicillin antimicrobial resistance was found in this study, in comparison to a study performed earlier in 2018 on isolates from poultry farmers and poultry slaughters (45.45% and 38%, respectively) [14]. High level of resistance to ampicillin was detected in Saudi Arabia and the United States of America (78.4% and 62%, respectively) [15,16].…”
Section: Discussionsupporting
confidence: 47%
“…Level of resistance to amoxicillin-clavulanic acid was 42.42% in 2018 [ 14 ]; the results of this study showed an increase up to 54.1%. Other results showed divergent percentages of resistance, 92.1% in Algeria and 4% in Tunisia [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 89%